2006
DOI: 10.2208/jsceseee.23.215s
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Deterioration of High Damping Rubber Bridge Bearing

Abstract: In recent years, high damping rubber (HDR) bridge bearings have become widely used because of the excellent ability to provide high damping as well as flexibility. However, there are few systematic studies on the deterioration problems of HDRs during their service life, and usually the long-term performance was not considered in the design stage. In this research, through accelerated thermal oxidation tests on HDR blocks, the property variations inside the HDR bridge bearing are examined. A deterioration predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Environmental factors like oxygen exposure, heat, and sunlight, which deteriorate physical properties of rubber bearings such as elasticity and strength, are usually not considered during the design process of rubber bearings. Understanding the degradation of the material properties is considered essential in their lifetime prediction [1][2][3]. As the service temperature rises, molecular changes take place, resulting in a loss of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors like oxygen exposure, heat, and sunlight, which deteriorate physical properties of rubber bearings such as elasticity and strength, are usually not considered during the design process of rubber bearings. Understanding the degradation of the material properties is considered essential in their lifetime prediction [1][2][3]. As the service temperature rises, molecular changes take place, resulting in a loss of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative degradation is the most important factor that determines durability in most engineering applications, including bridge rubber bearings, where the oxygen availability is limited by diffusion [2][3]. Itoh, et al [3,7] have evaluated the evolution of tensile mechanical properties (such as elongation at break and tensile strength) of different types of rubber compounds used for bridge bearings exposed to different ageing tests, including thermal oxidation, ozone, low temperature ozone, ultraviolet radiation, salt water, and acid rain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the lifetime of the elastomeric (e.g., high‐damping rubber bearings [HDRBs]) and sliding (e.g., flat sliding bearings [FSBs]) bearings, representing some of the most widely used types of isolation systems, ageing and air temperature are important factors that affect the degradation of rubber and friction coefficient of the sliding surface, respectively. The mechanical properties of the HDRBs change uniformly along the radial direction of the isolator in a relatively short time, until a stable equilibrium state is reached in the inner region bounded by an external critical depth, the latter being an exponential function of the temperature . The outer region is also affected by an oxidation process, related to time and depending on the amount of oxygen, which produces a degradation of properties whose effects diminish moving towards the critical depth.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the shear modulus of HDR compounds increases over time. Furthermore, accelerated thermal oxidation tests on HDR blocks were performed to clarify the long-term performance of HDRB [13,14]. A deterioration predication model was proposed to estimate the property profile.…”
Section: Introductionmentioning
confidence: 99%